Primary leiomyosarcoma of ovary: A rare malignancy as an incidental finding - Sujata Raychaudhuri; Dipti Sidam; Manjula Jain; Raina Chawla; Mukta Pujani; Ruchira Wadhwa (Wolters Kluwer Medknow Publications, 2022)
Primary leiomyosarcoma (PLMS) of the ovary is extremely rare tumors comprising 1% of ovarian tumors. About 3% of all ovarian malignancies are primary ovarian sarcomas. Only 72 cases have been reported till date. A 57-year-old postmenopausal female presented with abdominal pain for the last 6 months. Ultrasonography and MRI revealed a heterogeneously enhancing solid lobulated mass in the left adnexa abutting the fundus of the uterus and bowel loops. The endometrial cavity was normal. Ovarian markers CA 125, CEA, CA 19.9, and all hematological parameters were within normal limits. LDH was near normal (284 IU/ml). The specimen was sent for frozen section and a diagnosis of malignant spindle cell lesion of ovary was rendered. Histopathology of the ovarian mass revealed intersecting fascicles of tumor cells consisting of ovoid to spindle-shaped cells having a moderate amount of cytoplasm. Bizarre and atypical cells were seen singly dispersed and in small aggregates along with the brisk mitotic activity. Focal areas of necrosis and hemorrhage were also noted. Immunohistochemistry showed strong positivity for smooth muscle actin and Caldesmon while focal positivity for Desmin and Epithelial Membrane Antigen (EMA) was noted. The lesion was negative for Inhibin, Calretinin, and CD 117 and S100. The final diagnosis of primary ovarian Leiomyosarcoma was given based on histopathology and Immunohistochemistry. PLMS of the ovary are rare incidental findings in postmenopausal women. These are highly malignant tumors and carry a poor prognosis. Hence, early diagnosis and surgical treatment with cytoreduction improve patient survival.